RNA-Seq Identifies Marked Th17 Cell Activation and Altered CFTR Expression in Different Atopic Dermatitis Subtypes in Chinese Han Populations - Tian, Xin; Liu, Baoyi; Chen, Lijie; Xie, Yongyi; Liang, Jingyao; Yang, Yan; Shao, Lei; Zhang, Jing; Wang, Jianqin; Zhang, Xibao; Wu, Zhouwei; Liu, Yumei (Frontiers in Immunology, 2021)
Background: Patients with atopic dermatitis (AD) exhibit phenotypic variability in ethnicity and IgE status. In addition, some patients develop other allergic conditions, such as allergic rhinitis (AR), in subsequent life. Understanding the heterogeneity of AD would be beneficial to phenotype-specific therapies. Methods: Twenty-eight Chinese AD patients and 8 healthy volunteers were enrolled in the study. High-throughput transcriptome sequencing was conducted on lesional and nonlesional skin samples from 10 AD patients and matched normal skin samples from 5 healthy volunteers. Identification of differentially expressed genes (DEGs), KEGG pathway analyses, and sample cluster analyses were conducted in the R software environment using the DEseq2, ClusterProfiler, and pheatmap R packages, respectively. qRT-PCR, Western blotting, and ELISA were used to detect gene expression levels among subtypes. Correlation analysis was performed to further investigate their correlation with disease severity. Results: A total of 25,798 genes were detected per sample. Subgroup differential expression analysis and functional enrichment analysis revealed significant changes in the IL17 signaling pathway in Chinese EAD patients but not in IAD patients. DEGs enriched in cytokine-cytokine receptor interactions and gland secretion were considered to be associated with atopic march. Further investigations confirmed a marked IL17A upregulation in Chinese EAD with a positive relationship with total IgE level and AD severity. In addition, increased IL17A in AD patients with AR demonstrated a closer association with AR severity than IL4R. Moreover, AQP5 and CFTR were decreased in the lesions of AD patients with AR. The CFTR mRNA expression level was negatively associated with the skin IL17A level and AR severity. Conclusion: Our research characterized marked Th17 activation in Chinese EAD patients, and altered expression of IL17A, IL4R, AQP5, and CFTR in AD patients with AR was associated with AR severity. It partially explained the phenotypic differences of AD subtypes and provided potential references for endotype-targeted therapy.